Comparison of Buck and Synchronous Buck Converters for ANFIS-Controlled Li-Ion Fast Charging - SUHARININGSIH SUHARININGSIH; EPYK SUNARNO; EKA PRASETYONO; MOCHAMAD ARI BAGUS NUGROHO; KHAFIDZ BAYHAQI (Institut Teknologi Nasional, Bandung, 2025)
The research discusses the implementation of a fast charging system on Lithium-Ion batteries by comparing the performance of conventional Buck Converters and Synchronous Buck Converters. Charging is carried out using constant current (CC) and constant voltage (CV) methods with set points of 4A and 16.8V as the targets used, and is equipped with sensors to monitor voltage and current during the charging process. The system is controlled by the Adaptive Neuro Fuzzy Inference System (ANFIS) which is useful for maintaining charging stability at one battery specification with a full capacity of 4.2V voltage and 4A current. Test results show that ANFIS is able to maintain filling parameters within safe limits. In addition, the Synchronous Buck Converter provides better efficiency than conventional Buck Converters in terms of efficiency and controlling voltage fluctuations, so it is more optimal for use in Lithium-Ion battery fast charging systems.